Revision of the New World Species of the Millipede-Parasitic Genus Myriophora Brown (Diptera: Phoridae) - Hash, John M.; Brown, Brian V. (Zootaxa, 2015)
The New World species of the millipede-parasitic genus Myriophora Brown are revised. Sixty-five species based on the female sex are treated, mostly from the Neotropical Region. Of these, fifty-seven are new to science: Myriophora alexandrae sp. nov., Myriophora alienipennis sp. nov., Myriophora angustifascia sp. nov., Myriophora annetteae sp. nov., Myriophora annulata sp. nov., Myriophora bicuspidis sp. nov., Myriophora bilsae sp. nov., Myriophora bimaculata sp. nov., Myriophora borealis sp. nov., Myriophora brevitarsus sp. nov., Myriophora browni sp. nov. Hash, Myriophora brunneipleuron sp. nov., Myriophora communis sp. nov., Myriophora curvata sp. nov., Myriophora curvicacumen sp. nov., Myriophora dennisoni sp. nov., Myriophora discalis sp. nov., Myriophora diversa sp. nov., Myriophora dividida sp. nov., Myriophora dolionatis sp. nov., Myriophora flavicosta sp. nov., Myriophora fuscidorsum sp. nov., Myriophora gigantea sp. nov., Myriophora gobaleti sp. nov., Myriophora harwoodi sp. nov., Myriophora hebes sp. nov., Myriophora heratyi sp. nov., Myriophora inaequalisetarum sp. nov., Myriophora infirmata sp. nov., Myriophora jeffersoni sp. nov., Myriophora kerri sp. nov., Myriophora kungae sp. nov., Myriophora longisetarum sp. nov., Myriophora luteitergum sp. nov., Myriophora magnilabellum sp. nov., Myriophora misionesensis sp. nov., Myriophora nigra sp. nov., Myriophora nigralinea sp. nov., Myriophora obscuritergum sp. nov., Myriophora pallida sp. nov., Myriophora parva sp. nov., Myriophora pectinata sp. nov., Myriophora perpendicularis sp. nov., Myriophora plana sp. nov., Myriophora porrasae sp. nov., Myriophora porrecta sp. nov., Myriophora reminatis sp. nov., Myriophora scopulata sp. nov., Myriophora simplex sp. nov., Myriophora sinesplendida sp. nov., Myriophora smithi sp. nov., Myriophora spicaphora sp. nov., Myriophora spicaticonus sp. nov., Myriophora tenuis sp. nov., Myriophora uruguaiensis sp. nov., Myriophora vancouverensis sp. nov., Myriophora wellsorum sp. nov. The first key to the species of Myriophora is provided.